Diversity in action: exchange of perspectives and reflections on taxonomies of individual differences. (19th April 2018) - Uher, Jana; Trofimova, Irina; Sulis, William; Netter, Petra; Pessoa, Luiz; Posner, Michael I.; Rothbart, Mary K.; Rusalov, Vladimir; Peterson, Isaac T.; Schmidt, Louis A.
Abstract : Throughout the last 2500 years, the classification of individual differences in healthy people and their extreme expressions in mental disorders has remained one of the most difficult challenges in science that affects our ability to explore individuals' functioning, underlying psychobiological processes and pathways of development. To facilitate analyses of the principles required for studying individual differences, this theme issue brought together prominent scholars from diverse backgrounds of which many bring unique combinations of cross-disciplinary experiences and perspectives that help establish connections and promote exchange across disciplines. This final paper presents brief commentaries of some of our authors and further scholars exchanging perspectives and reflecting on the contributions of this theme issue. This article is part of the theme issue 'Diverse perspectives on diversity: multi-disciplinary approaches to taxonomies of individual differences'.